The organization and function of endogenous antinociceptive systems - Sandkühler, Jürgen (Progress in neurobiology, 1996)
Much progress has been made the understanding of endogenous pain controlling systems. Recently, new concepts and ideas which are derived from neurobiology, chaos research and from research on learning and memory have been introduced into pain research and shed further light on the organization and function of endogenous anti nociception. These most recent developments will be reviewed here. Three principles of endogenous antinociception have been identified, as follows. (1) Supraspinal descending inhibition: the patterns of neuronal activity in diencephalon, brainstem and spinal cord during antinociceptive stimulation in midbrain periaqueductal gray (PAG) or medullary nucleus raphe magnus have now been mapped on the cellular level, using the c-Fos technique. Results demonstrate that characteristic activity patterns result within and outside the PAG when stimulating at its various subdivisions. The descending systems may not only depress mean discharge rates of nociceptive spinal dorsal horn neurons. but also may modify harmonic oscillations and nonlinear dynamics (dimensionality) of discharges. (2) Propriospinal, heterosegmental inhibition: antinociceptive, heterosegmental interneurons exist which may be activated by noxious stimulation or by supraspinal descending pathways. (3) Segmental spinal inhibition: a robust long-term depression of primary afferent neurotransmission in Aδ fibers has been identified in superficial spinal dorsal horn which may underlie long-lasting antinociception by afferent stimulation, e.g. by physical therapy or acupuncture.
Online 26 October 2004
Elektronische Reproduktion der Druck-Ausgabe
Gesehen am 03.05.2021